Synthesis and Characterization of Some New Derivatives of 8-Chlorothiophyllìne by Microwave-Assist Suzuki-Miyaura Coupling Reaction - Salwa R. Abdul-Ameer (Journal of Global Pharma Technology, 2018)
Some new derivatives of 8-Chlorothiophyllìne (8-CTh) synthesized by Suzuki reactions when react 8-CTh with hydrazine to give 8-hydrazinyl thiophyllìne. This compound reacts with 4-bromo benzaldehyde to give imine compound. The microwave-promoted Suzuki-Miyaura coupling of the latter compound with different aryl boronìc acids gave (3-9) compounds with good to excellent yields. This reaction was checked by thin‐layer chromatography (TLC) method. All new compounds were characterized by melting points, elemental analysis, and FT‐IR, 1H, 13C-NMR and 2D-NMR spectroscopy. The antibacterial action of these derivatives was also determined.Keywords: 8-Chlorothiophyllìne, Suzuki reaction, Microwave, Antibacterial, Antifungal.